Vermicompost enrichment using organic wastes: Nitrogen content and mineralization - Ali Askari; Ali Khanmirzaei; Shekoofeh Rezaei (International Journal of Recycling of Organic Waste in Agriculture)
Purpose This study performed a feasibility assessment of nitrogen enrichment by some organic wastes through vermicomposting as well as its release as a bioavailable form over time. Methods Soybean and canola wastes as well as the dairy blood powder of industrial slaughterhouse were used as organic wastes to enrich the vermicompost. Composted materials were incubated for nitrogen mineralization kinetic assessment by adjusting moisture content to 50% at 30 ˚C for 80 days. During the incubation, moisture was maintained by weighing. Subsamples were collected after 1, 5, 10, 20, 40, 60, and 80 days of incubation. Results Among the treatments, those for 25% dairy blood powder contained the highest nitrogen content (4.95 and 3.70% for chicken and cow blood powder, respectively). Nitrogen mineralization through 80 days of incubation ranged from 2.23% (for 50% canola waste treatment) to 2.57% (for 25% blood powder) of the total nitrogen. The mineralization rate ranged from 4.24 and 3.62 mg kg-1 day-1 for the compost containing 25% chicken and cow blood powder, respectively, to 0.94 and 0.84 mg kg-1 day-1 in canola and soybean waste, respectively, whereas those for the control treatment equaled 0.81 mg kg-1 day-1. Conclusion Composts containing 25% blood powder were acceptable in terms of quantity and nitrogen release over time, and can serve as a reliable source of available nutrients in the soil.